Potential of Pseudomonas yamanorum for the valorization of municipal biosolids - Jordan Lussier; Linson Lonappan; Hubert Cabana (Water Quality Research Journal, 2023)
It is generally accepted that some trace organic contaminants (TrOCs) pass through the wastewater treatment process without being properly treated and find their way into waterbodies. These molecules can also be concentrated within the biosolids (BS) through adsorption. The presence of TrOCs in BS, which are then commonly used as soil amendments in agriculture, may affect plant growth and viability. The potential risks posed by TrOCs are usually ignored because they are present in low concentrations and mostly have relatively short half-lives. However, the continuous addition of these substances in water sources and on farmlands makes them pseudo-persistent. To reduce the concentrations of selected TrOCs from these BS, Pseudomonas yamanorum LBUM636 (PY) was tested with and without a commercial bacterial blend of Bacillus spp. (BC). About 60% removal of atrazine was achieved using PY-amended BS. Bioslurries inoculated with PY had relatively high laccase activity at about 2,200 U/L. Laccase activity was seven times higher in samples where BC was also present, which suggests a synergistic effect between BC and PY. Concentrations of phenazine-1-carboxylic acid, an antibiotic with a biopesticide effect, were also relatively important in PY-inoculated bioslurries. HIGHLIGHTS Pseudomonas yamanorum was successfully grown on municipal biosolids (BS) with/without the addition of a commercial blend of Bacillus spp.; P. yamanorum induced the reduction of atrazine from BS.; Phenazine-1-carboxylic acid was produced in P. yamanorum inoculated BS.;